Analisis Kepatuhan Wajib Pajak Orang Pribadi (WPOP) dalam Memenuhi Kewajiban Pajak di Kantor Pelayanan Pajak (KPP) Pratama Depok Sawangan - Adina Putri; Diah Armeliza; Dwi Handarini (Indo Publishing, 2025)
This study aims to determine the level of compliance of WPOP in fulfilling their tax obligations at the Depok Sawangan Tax Office. It also provides recommendations for improvement. This study uses the Depok Sawangan Tax Office as its research object. This study is qualitative in nature with a descriptive analysis approach. The data sources used are secondary and primary data. The results of this study show that compliance in fulfilling tax obligations at the Depok Sawangan Tax Office is still relatively low. In addition, there are several inhibiting factors, such as server congestion during the reporting period, a limited number of officers causing long queues, and a lack of socialization, resulting in WPOP's limited understanding of taxation. The recommended strategies include increasing the capacity of the reporting system to overcome server congestion, adding service officers to reduce queues, and intensifying tax socialization to increase WPOP's understanding